Two Functions of Perception in Kant - Laiho, Hemmo (Con-Textos Kantianos. International Journal of Philosophy, 2020)
Kant uses terms translatable as ‘synthesis’ and ‘perception’ in different ways in different contexts, which suggests that there are different kinds of synthesis and perception. I propose that there are two main basic functions of perception according to Kant: that of singling out a thing and that of getting perceptually informed about the configuration of the thing’s perceptible features. I arguethat the first function is not dependent on the kinds of syntheses Kant analyzes in the Critique of Pure Reason but grounds any such synthesis. I also argue that if singling out a thing is considered to involve synthesis, then the term ‘synthesis’ is identified with a unification of sensory information itself, which is not of much consequence for the transcendental philosopher. The paperalso aims to clarify what ‘manifold’ consists in and what the starting point of the ‘synthesis in apprehension’ might be.